Sustainable Product Innovation as the Main Driver of Business Growth in the Green Economy Era - Devi Susiati; Siti Aisyah; Ilham Sentosa; Hotnida Nainggolan; Septianti Permatasari Palembang (West Science Business and Management, 2023)
In the era of the green economy, sustainable product innovation is becoming a key factor in determining how businesses thrive. The present bibliometric analysis delves into the scholarly terrain concerning sustainable product innovation, elucidating its principal contributors, research themes, and business consequences. Leading scholarly databases provided the data, which were then examined using the bibliometric software program VOSviewer. Influential books, prolific writers, and research hubs were found through the investigation. Among the notable discoveries are foundational studies on strategic factor markets by Barney (1986), corporate sustainability beyond the business case by Dyllick & Hockerts (2002), and business models and innovation by Teece (2010). Research clusters were revealed through co-citation analysis, underscoring the complex character of sustainable product innovation. Topics including competitive advantage, sustainable entrepreneurship, corporate social responsibility, sustainable supply chains, and innovative business models were covered by clusters. networks of collaboration and prolific writers. Popular themes that emerged from the keyword analysis included "business practice," "innovation," "corporate sustainability," and "sustainable business models." In the air were phrases like "circular economy," "sustainable consumption," and "social responsibility." These results offer a thorough synopsis of the developing body of knowledge regarding sustainable product innovation in academia.